2016
DOI: 10.1016/j.parint.2015.10.008
|View full text |Cite
|
Sign up to set email alerts
|

Development of multiplex serological assay for the detection of human African trypanosomiasis

Abstract: Human African trypanosomiasis (HAT) is a disease caused by Kinetoplastid infection. Serological tests are useful for epidemiological surveillance. The aim of this study was to develop a multiplex serological assay for HAT to assess the diagnostic value of selected HAT antigens for sero-epidemiological surveillance. We cloned loci encoding eight antigens from Trypanosoma brucei gambiense, expressed the genes in bacterial systems, and purified the resulting proteins. Antigens were subjected to Luminex multiplex … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
21
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(23 citation statements)
references
References 20 publications
2
21
0
Order By: Relevance
“…However, there are still some challenges in this area. In the future, therefore, we will specifically need to: [140] Develop new, specific biomarkers: a) which will provide serodiagnosis of trichinellosis during the early stage of disease (3e4 weeks between Trichinella infection and specific antibody positivity) [213], b) for Trypanosoma brucei rhodesiense and Trypanosoma brucei gambiense infections considering the fact that these parasites express variable surface antigens which significantly limits diagnostic usefulness of serological examination [214], c) for Toxoplasma gondii infection suitable to divide recent from past infections and replace a panel of tests (Toxoplasma gondii serologic profile (TSP)) which is still in use for this purpose [215], d) which will allow serological differentiation between Toxocara canis and Toxocara cati (or Toxocara malaysiensis) infections [216]. Develop scalable tests, particularly for use in field situations (e.g.…”
Section: Research Priorities For the Futurementioning
confidence: 99%
“…However, there are still some challenges in this area. In the future, therefore, we will specifically need to: [140] Develop new, specific biomarkers: a) which will provide serodiagnosis of trichinellosis during the early stage of disease (3e4 weeks between Trichinella infection and specific antibody positivity) [213], b) for Trypanosoma brucei rhodesiense and Trypanosoma brucei gambiense infections considering the fact that these parasites express variable surface antigens which significantly limits diagnostic usefulness of serological examination [214], c) for Toxoplasma gondii infection suitable to divide recent from past infections and replace a panel of tests (Toxoplasma gondii serologic profile (TSP)) which is still in use for this purpose [215], d) which will allow serological differentiation between Toxocara canis and Toxocara cati (or Toxocara malaysiensis) infections [216]. Develop scalable tests, particularly for use in field situations (e.g.…”
Section: Research Priorities For the Futurementioning
confidence: 99%
“…The relatively low fluorescence intensity obtained for these last five antigens could be explained either by a weak coupling of the antigens to the fluorescent microspheres or by the conformation of the coated antigens that made the HisTag inaccessible to the anti-HisTag antibodies. Discrepancies between the coating measurement with anti-HisTag antibodies and the efficacy of coupling antigens in diagnostic tests have also been described by others 18 , so we decided to perform serum reactivity assays for the eight antigens. The results obtained confirmed that coupling controls using anti-HisTag antibodies cannot accurately predict the reactivity of the antigen during these experiments since high fluorescence intensities were obtained for antigens with low fluorescence intensities using anti-HisTag antibodies (Figs.…”
Section: Discussionmentioning
confidence: 97%
“…Antigens enolase, PFR1 and PFR2 were also excluded due to low fluorescence intensities for positive sera (lack of sensitivity). The exclusion of seven out of the eight antigens originally selected in this study was unexpected, as several of these antigens (such as Rotat1.2 20 and ISG65 18 ) have already been used by other teams developing diagnostic tools for trypanosomosis. The reasons for the lack of efficacy remain unidentified.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is possible that other antigens that were either not included or had not been identified at that time could perform equally well or better than assessed in the present study. For example, the flagellar calcium-binding protein TB-17 [20,60], the Gene Related to Expression Site Associated Gene (GRESAG) 4, and transferrin receptor subunits ESAG 6 and 7 have also been suggested as potential candidates [20]. Since the most reactive antigens include the native VSG LiTat 1.3 and VSG LiTat 1.5 antigens, which are costly and difficult to produce, one approach might be to generate recombinant versions of these proteins.…”
Section: Discussionmentioning
confidence: 99%